EFEKTIFITAS PENGGUNAAN MEDIA LAGU DALAM PENGUASAAN GOI SISWA SMA - nissa, alif fatun; Yulia, Nova (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
This research is motivated by difficulties with remembering goi.  This study aims to find out whether the use of song media is effective in mastering the goi of high school students. This research is a quantitative study with a pseudo-type of the experiment. The design used in this study is a posttest-only control group design. The population in this study was all students of class X social studies sman 1 X Koto consisting of 4 classes totaling 120 students. The sampling technique in this study used purposive sampling technique. The posttest-only sample in this study was class X social studies 1 which amounted to 30 students, divided into experimental classes of 15 students and control classes of 15 students. The instruments used in this study were in the form of an objective test of 20 questions and a 5-question fill-in test. Based on the hypothesis test at a significant level of 0.05, the results of the calculation of > ttabel (4.88 > 2.04 were obtained. So it can be concluded that the media of Japanese songs is effective against the goi ability of students of SMAN 1 X Koto.